Pengaruh Kualitas Pelayanan, Kepuasan Nasabah dan Citra Perusahaan Terhadap Loyalitas Nasabah Pada PT. Bank Central Asia KCU Makassar - Ahmad Fadhli Edar; Muhammad Asdar; Abdul Razak Munir (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2019)
This study aims to determine to determine the effect of service quality, customer satisfaction and corporate image of customer loyalty at PT. Bank Central Asia KCU Makassar. The type of data used in this study is quantitative data in the form of answers given by respondents to the statement in the questionnaire. Source of data used in this research is primary data, that is data of respondent's answer to question in questionnaire. The results showed that partially the quality of service, customer satisfaction, and corporate image have a positive and significant impact on customer loyalty. As for the simultaneous quality of service, customer satisfaction and corporate image have a positive and significant impact on customer loyalty at PT. Bank Central Asia KCU Makassar.